Metabolic regulatory network alterations reveal different therapeutic effects of cisplatin and Rhizoma paridis saponins in Lewis pulmonary adenoma mice. Issue 116 (13th December 2016) - Qiu, Peiyu; Man, Shuli; Yang, He; Liu, Yuanxue; Liu, Zhen; Ma, Long; Yu, Peng; Gao, Wenyuan
Abstract : Metabonomics is used to compare the metabolic profiling of RPS and DDP in Lewis pulmonary adenoma mice; RPS is found to be a potent anticancer agent through inhibiting cancer cellular metabolism to suppress metastases in murine lung adenocarcinoma. Abstract : Lung cancer is the leading cause of tumor-related mortality in the world. Cisplatin (DDP) is regarded as a first-line treatment for lung cancer. However, toxicity has limited its application. Rhizoma paridis saponins (RPS) have been found to show inhibition of pulmonary adenoma in our previous research. In this experiment, we used metabonomics to compare the metabolic profiling of RPS and DDP in Lewis pulmonary adenoma mice, which promoted the application of RPS in the future. According to 1 H-NMR and GC/MS detection, RPS treatment decreased most lipid compound levels and concentration of lactic acid. Meanwhile, RPS increased the concentration of glutamate and glucose. In contrast, DDP treatment increased the levels of lipids and decreased the concentration of glucose. For the metabolic enzyme related genes analysis, RPS and DDP regulated the p53/mTOR-c-Myc-HIF-1α network to decrease GLUT1, HK2, PKM2 and LDHA genes. Meanwhile, the ascendant mRNA of p53 raised GLS levels and suppressed the ATP product. What's more, RPS treatment decreased mRNA levels of FASN to repress lipogenesis. In contrast, DDP treatment increased lipogenesis to induce pulmonary metastasis. Taken together, RPS is a potent anticancer agent through inhibiting cancer cellular metabolism to suppress metastases in murine lung adenocarcinoma which promotes the application of RPS in the future.